The body and military masculinity in Late Qing and early republican China: the art of governing soldiers - Schillinger, Nicolas (Lexington Books, 2016)
This study examines the cultural effects of China's adoption of a European military model in the late nineteenth and early twentieth centuries. It argues that there was a conceptual reconfiguration of Chinese masculinity and citizenship and focuses on how the body was conceived, shaped by physical fitness and medical practices, and controlled.